2014
DOI: 10.1371/journal.pone.0088601
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin Alpha Reduces Oxidative Stress and Chronic Inflammation in Atherosclerotic Lesions of Apo E Deficient Mice in Experimental Renal Failure

Abstract: BackgroundCardiovascular morbidity and mortality is very important in patients with chronic renal failure. This occurs even in mild impairment of renal function and may be related to oxidative stress and chronic inflammation. The nephrectomized apo E knockout mouse is an accepted model for evaluating atherosclerosis in renal dysfunction. Erythropoietin derivates showed anti-oxidative and anti-inflammatory effects. Therefore, this study evaluates the effects of Darbepoetin on markers of oxidative stress and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Epo diminished the production of inflammatory cytokines [18] and oxidative stress [19] and had beneficial effects on the morphology of atherosclerotic lesions of apo E knockout mice via reduction of the lipid content of macrophages and the subsequent formation of foam cells [20]. Darbepoetin alpha, a long-acting ESA, suppressed oxidative stress, inflammation in the heart and aorta, plaque stage, and plaque cholesterol content in subtotally nephrectomized rats [21]. The positive association of nonuse of ESA from the predialysis stage with obstructive CAD needing coronary revascularization found in this study would indicate the inhibitory effect of ESA on the progression of coronary plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Epo diminished the production of inflammatory cytokines [18] and oxidative stress [19] and had beneficial effects on the morphology of atherosclerotic lesions of apo E knockout mice via reduction of the lipid content of macrophages and the subsequent formation of foam cells [20]. Darbepoetin alpha, a long-acting ESA, suppressed oxidative stress, inflammation in the heart and aorta, plaque stage, and plaque cholesterol content in subtotally nephrectomized rats [21]. The positive association of nonuse of ESA from the predialysis stage with obstructive CAD needing coronary revascularization found in this study would indicate the inhibitory effect of ESA on the progression of coronary plaque.…”
Section: Discussionmentioning
confidence: 99%
“…23 In accordance with our findings, Arend et al reported a significant decrease in CRP expression in darbepoetin-α-treated ApoE -/mice. 24 In a study performed by Huang et al it was reported that basal serum IL-6 levels of ApoE knockout mice were akin to those in C57BL mice. 25 Histamine and its receptors are formed in atherosclerotic lesions, and their signaling and following proinflammatory and proatherogenic gene expression are involved in the progress of atherogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Arend et al reported that ICAM protein expression in the aorta did not differ markedly between the nephrectomized or darbepoetin-α-treated groups, neither in the intramyocardial arteries and aortic plaque nor in the aortic endothelium of ApoE -/mice. 24 Endothelial function is impaired in the earlier stages of atherogenesis and is strongly correlated with several risk factors. Endothelial dysfunction predisposes to longterm atherosclerotic lesions and has been proposed as an important diagnostic and prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Aizawa et al suppressed [33] increased urea nitrogen after epoetin beta pegol (CERA) in Thy-1-GN rats. Arend et al [34] considered the dose-dependent adverse effects of high darbepoetin treatment as elevated serum urea in nephrectomized apo E knockout mice. Ahmadiasl et al significantly decreased [35] blood SOD, GPx, and urea levels and increased TAC level after treatment with Epo and MEL in renal IR injury of male rats.…”
Section: Discussionmentioning
confidence: 99%